2020
DOI: 10.1177/0706743720940565
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Suicide Mortality in Canada by Sex and Age Group, 1981 to 2017: A Population-Based Time Series Analysis: Tendances de la mortalité par suicide au Canada selon le sexe et le groupe d’âge, 1981 – 2017 : Une analyse de séries chronologiques dans la population

Abstract: Objectives: Suicide is a complex global public health issue. The objective of this study was to assess time trends in suicide mortality in Canada by sex and age group. Methods: We extracted data from the Canadian Vital Statistics Death Database for all suicide deaths among individuals aged 10 years and older based on International Statistical Classification of Diseases and Related Health Problems, Ninth Revision (E950-959; 1981 to 1999) and International Statistical Classification of Diseases and Related Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…19,20 Recent Canadian research reported rising suicide rates among females aged 10-24 and 45-64 years. 2 Our research suggests that this may reflect rising rates of suicide by suffocation among females younger than 65 years. Substitution of less lethal means of suicide (e.g., poisoning) with more lethal ones (e.g., suffocation) over time among younger females might explain this increase.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…19,20 Recent Canadian research reported rising suicide rates among females aged 10-24 and 45-64 years. 2 Our research suggests that this may reflect rising rates of suicide by suffocation among females younger than 65 years. Substitution of less lethal means of suicide (e.g., poisoning) with more lethal ones (e.g., suffocation) over time among younger females might explain this increase.…”
Section: Discussionmentioning
confidence: 75%
“…The increasing rate of suicide by suffocation among some sociodemographic groups in Canada may partially explain why the overall suicide rate has not continued to decrease in recent years. 2 Increasing rates of suicide by suffocation have also been observed in other countries; for instance, Norway and the United States. 19,20 Recent Canadian research reported rising suicide rates among females aged 10-24 and 45-64 years.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations